Kecemasan dan Metode Pengendaliannya - Abdul Hayat (UIN Antasari Banjarmasin, 2017)
Anxiety is part of the living conditions, meaning that there are concerns on everyone. Anxiety is a source of motivation to act towards progress and success in life, when anxiety was in a normal condition ( normal anxiety ), but high anxiety beyond normal limits ( neurotic anxiety ) she would offend stability of self and life balance. Therefore it needs to be controlled by the method of controlling anxiety. Many prusedures and anxiety control methods designed by psychotherapists and kaunseling, so we can use whichever is thought to be more suitable and easy to use. Privacy will be healthier if free from neurotic anxiety.